2016
DOI: 10.2174/1568026616666151015093406
|View full text |Cite|
|
Sign up to set email alerts
|

Biomarkers in the Management of Difficult Asthma

Abstract: Difficult asthma is a heterogeneous disease of the airways including various types of bronchial inflammation and various degrees of airway remodeling. Therapeutic response of severe asthmatics can be predicted by the use of biomarkers of Type2-high or Type2-low inflammation. Based on sputum cell analysis, four inflammatory phenotypes have been described. As induced sputum is time-consuming and expensive technique, surrogate biomarkers are useful in clinical practice.Eosinophilic phenotype is likely to reflect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 133 publications
(178 reference statements)
0
53
0
1
Order By: Relevance
“…Although the treatment of asthma is moving forward with the onset of the biological therapy era, leading to greater opportunities for individualized treatment, identification of new molecular targets and biomarkers reflecting them is needed. Currently, assessment of airway type 2 inflammation is related with validated biomarkers of eosinophilic airway inflammation, such as blood eosinophil count, sputum eosinophilia, FeNO, serum periostin and IgE . We also checked blood eosinophil count and FeNO, and observed that following the allergen exposure, these biomarkers only exhibited a significant increase in the AA group, without changes in HS.…”
Section: Discussionmentioning
confidence: 94%
“…Although the treatment of asthma is moving forward with the onset of the biological therapy era, leading to greater opportunities for individualized treatment, identification of new molecular targets and biomarkers reflecting them is needed. Currently, assessment of airway type 2 inflammation is related with validated biomarkers of eosinophilic airway inflammation, such as blood eosinophil count, sputum eosinophilia, FeNO, serum periostin and IgE . We also checked blood eosinophil count and FeNO, and observed that following the allergen exposure, these biomarkers only exhibited a significant increase in the AA group, without changes in HS.…”
Section: Discussionmentioning
confidence: 94%
“…Although not currently feasible for widespread use, induced sputum is generally considered the gold standard noninvasive method for assessing airway inflammation in asthma to identify inflammatory phenotype and could be valuable in phenotyping patients with asthma. 25 Moreover, sputum analysis allows for assessment of not only eosinophil levels but also other inflammatory cells (particularly neutrophils, which are not available from blood).…”
Section: Panel Consensus On Phenotypingmentioning
confidence: 99%
“…The exact functional role of each individual cytokine in the pathogenesis of the disease remains to be fully established. [9,10] The potential role of type 2 T-helper cell-cytokines in asthma is increasingly being recognized in particular interleukin -4, interleukin -5 and interleukin -13. Th2 cells are thought to control the growth and effectors function of those cell types that are involved in allergic inflammatory responses in asthmatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…From these inflammatory cells the eosinophil is considered a key effectors cell in the pathogenesis of allergic inflammation in asthma. [7][8][9][10] IL-5 seems to be the primary cytokine involved in the production, differentiation, maturation and activation of eosinophils. [13,14] The ant-inflammatory effects of glucocorticoids in asthma include modulation of cytokine and chemokine production, inhibition of eicosanoid synthesis, marked inhibition of accumulation of basophils, eosinophils and other leukocyte in lung tissue and decreased vascular permeability.…”
Section: Introductionmentioning
confidence: 99%